Investigation of a foodborne outbreak of Shigella sonnei in Ireland and Northern Ireland, December 2016: the benefits of cross-border collaboration and commercial sales data. (May 2020) - O'Brien, S.; Garvey, P.; Baker, K.; Brennan, M.; Cormican, M.; Cuddihy, J.; De Lappe, N.; Ellard, R.; Fallon, Ú.; Irvine, N.; Murphy, S.; O'Brien, D.; et al.
Abstract: Objectives: To describe a cross-border foodborne outbreak of Shigella sonnei that occurred in Ireland and Northern Ireland (NI) in December 2016 whilst also highlighting the valuable roles of sales data and international collaboration in the investigation and control of this outbreak. Study design: A cross-border outbreak control team was established to investigate the outbreak. Methods: Epidemiological, microbiological, and environmental investigations were undertaken. Traditional analytical epidemiological studies were not feasible in this investigation. The restaurant chain provided sales data, which allowed assessment of a possible increased risk of illness associated with exposure to a particular type of heated food product (product A). Results: Confirmed cases demonstrated sole trimethoprim resistance: an atypical antibiogram for Shigella isolates in Ireland. Early communication and the sharing of information within the outbreak control team facilitated the early detection of the international dimension of this outbreak. A joint international alert using the European Centre for Disease Control's confidential Epidemic Intelligence Information System for Food- and Waterborne Diseases and Zoonoses (EPIS-FWD) did not reveal further cases outside of the island of Ireland. The outbreak investigation identified that nine of thirteen primary case individuals had consumed product A from one of multiple branches of a restaurant chain located throughout the island of Ireland. Product A was made specifically for this chain in a food production facility in NI. S. sonnei was not detected in food samples from the food production facility. Strong statistical associations were observed between visiting a branch of this restaurant chain between 5 and 9 December 2016 and eating product A and developing shigellosis. Conclusions: This outbreak investigation highlights the importance of international collaboration in the efficient identification of cross-border foodborne outbreaks and the value of using sales data as the analytical component of such studies. Highlights: 21 cases of illness were associated with a foodborne outbreak of Shigella sonnei . Of 13 primary cases, where exposure information was available, 69% (n = 9) reported visiting a branch of the restaurant chain. Of 13 primary cases, where exposure information was available, 69% (n = 9) reported consuming a type of heated food product. Sales data showed an elevated risk of illness associated with consuming this type of heated food product (product A). Whole genome sequencing confirmed microbiological link between cases.